Accelerometer-measured physical activity and sample-based frailty in older women: does pattern really matter? - Li, Ting; Zong, Guanyang; Peng, Pan; Wang, Shiqiang; Cheng, Bin (Frontiers in Public Health, 2024)
Little is currently understood about the relationship between patterns of physical activity (PA) and frailty, including its various subdomains. The aim of this study was to investigate the relationship between patterns of physical activity and frailty and its various subdomains in community-dwelling older women.A cross-sectional study investigated the association between physical activity and frailty in 1099 women aged 60-70. Triaxial accelerometers were used to measure bouted PA (at least 10 min in duration) and sporadic PA (<10min in duration). Fried's frailty phenotype was utilised to evaluate the status of frailty. Data were analysed using logistic regression and receiver operating characteristic curve.Bouted moderate-to-vigorous PA (MVPA) and sporadic MVPA were associated with decreased odds of being pre-frail and frail, the optimal cutoffs were 6, 19.7 for pre-frail, and 6.6, 19.4 min/d for frail, respectively. Bouted light PA (LPA) were associated with decreased odds of being pre-frail, the optimal cutoffs were 170.2 min/d. Additionally, bouted and sporadic MVPA were associated with decreased odds of being slowness, the optimal cutoffs were 5, and 19.1 min/d, respectively. Sporadic MVPA was associated with decreased odds of being exhaustion, the cutoff was 19.7 min/d. Bouted MVPA and LPA were associated with decreased odds of being low PA, the cutoffs were 4.4 and 163.2 min/d, respectively.Any MVPA, regardless of bout duration, could be used as a suitable PA program to improve and prevent frailty in older women such as bouted MVPA (4-5 times/week) or sporadic MVPA (20 min/d). The improvement effect of bouted and sporadic MVPA on the frailty of older people may not be affected by the subdomain. Additionally, bouted LPA was suitable for the management of prefrailty.